PEMANFAATAN BAMBU OLEH MASYARAKAT DESA BABANE KECAMATAN SAMALANTAN KABUPATEN BENGKAYANG - Usman, . (Universitas Tanjungpura, 2019)
Bamboo is a very useful plant for the economic life of the community. Until now, bamboo has been used very widely, ranging from the use of the simplest technology to be used high technology on an industrial scale. Traditionally, bamboo is commonly used for various purposes such as household appliances, handicrafts and groceries. The purpose of this study was to determine the type of bamboo plants and their utilization by the community in Babane Village, Samalantan District, Bengkayanag Regency. The method used in this research is direct survey method in the field. Data analysis technique is done by using descriptive explorative analysis by describing bamboo plant species. The results of this study can be found that 8 species of 4 genera: Bambusa vulgaris (yellow Tarenk), Bambusa multiplex (Aur) Dendocalamus asper (Betung), Schizotachyum zollinggeri (Buluh), Schizotachyum lima (pesak), Gigantochloa sp (Munti), Gigantochloa altroviolacea (Tarenk), Gigantochloa balui (Bangking). And its use is the making of webbing by artisans, antenna poles, animal cages, boards, making vegetables from rizom (bamboo shoots), and as an ornamental plant in the yard.Keywords : Babane Village, Bamboo, ornamental plant.